Efektifitas Lembaga Amil Zakat (LAZ) DASI NTB Dalam Mempertahankan dan Meningkatkan Jumlah Muzakki di Kota Mataram - Baiq Wita Pradika; Akhmad Jufri; Moh. Huzaini (Postgraduate, University of Mataram, 2025)
The purpose of the study was to determine the effectiveness of the strategy of the Amil Zakat Institution (LAZ) DASI NTB in maintaining and increasing the number of Muzakki in Mataram City. This research uses a qualitative approach with descriptive methods. The data collection techniques used are observation, interview and documentation. Determination of informants in this study using purposive and snowball. The data validity method used is the triangulation method. Data analysis methods use data collection, data reduction, data presentation, and drawing conclusions. The indicators of effectiveness measurement are program understanding, on target, on time, achieving goals, and real changes. The results of the five indicators in terms of increasing and maintaining the number of Muzakki, direct strategies through socialization are very effective because they achieve all five indicators, direct strategies through funding are effective but not as effective as socialization and indirect strategies through social media and websites are less effective because there are several indicators that are not achieved.